Ceftriaxone-Induced Fatal Anaphylaxis Shock at an Emergency Department: A Case Report - Imam, Ethar Abdelmageed; Ibrahim, Mohamed Izham Mohamed (Journal of Pharmacy Practice and Community Medicine)
Anaphylaxis in adults caused by medications such as antibiotics are quite common. To best of our knowledge, the case of anaphylaxis caused by ceftriaxone in our hospital and clinical practice is rare and especially among Saudi patients. A 31-years old Arab female patient was admitted to the emergency (ER) department due to influenza symptoms. Patient was suspected having pneumonia after examination. History indicated that she did not have penicillin allergy in the past, no history of any other concomitant medications, and no other comorbidities. Patient was febrile. At ER department, she was given ceftriaxone 1 g intravenous (IV) and within 15 min the patient started to complain from shortness of breath, bronchospasm and developed irregularity of the vital signs. Patient was suspected experiencing anaphylactic shock. Ceftriaxone was discontinued. Aggressive management started immediately; patient was given oxygen, IM adrenaline, IV hydrocortisone, IV bolus of normal saline, IV ringer lactate, IV pheniramine, and IV ranitidine. Tepid water sponging was provided to control the fever. After resuscitative treatment, patient was stabilized and the vital signs were good. The patient then was moved out to the medical ward. Health care professionals at the Emergency Department should be mindful of the anaphylaxis possibility with patient receiving antibiotics in the cephalosporin group.
Keywords: Anaphylactic Shock; Ceftriaxone; Hypersensitivity; Resuscitative Treatment; Penicillin